A pilot randomized controlled trial of the Occupational Goal Intervention method for the improvement of executive functioning in patients with treatment-resistant schizophrenia. (30th November 2016) - Vizzotto, Adriana D.B.; Celestino, Diego L.; Buchain, Patricia C.; Oliveira, Alexandra M.; Oliveira, Graça M.R.; Di Sarno, Elaine S.; Napolitano, Isabel C.; Elkis, Helio
Abstract: Schizophrenia is a chronic disabling mental disorder that involves impairments in several cognitive domains, especially in executive functions (EF), as well as impairments in functional performance. This is particularly true in patients with Treatment-Resistant Schizophrenia (TRS). The aim of this study was to test the efficacy of the Occupational Goal Intervention (OGI) method for the improvement of EF in patients with TRS. In this randomized, controlled, single-blind pilot study, 25 TRS patients were randomly assigned to attend 30 sessions of either OGI or craft activities (control) over a 15-week period and evaluated by the Behavioural Assessment of the Dysexecutive Syndrome (BADS) as the primary outcome and the Direct Assessment of Functional Status (DAFS-BR) as well as the Independent Living Skills Survey (ILSS-BR) as secondary outcomes, all adapted for the Brazilian population. The Positive and Negative Syndrome Scale (PANSS) was used for monitoring symptom severity. Results showed significant statistical differences, favoring the OGI group in terms of improvement on the BADS, both in subtests (Action Program and Key Search) and the total score. Improvements in EFs were observed by families in various dimensions as measured by different subtests of the ILSS-BR inventory. The OGI group showed no significant results in secondary outcomes (DAFS-BR) except in terms of improvement of communication skills. Although preliminary, our results indicate that the OGI method is efficacious and effective for patients with TRS. Highlights: The Occupational Goal Intervention (OGI) is a method for the improvement of Executive Functions (EF). Patients with schizophrenia treated with OGI or showed better improvements in EF than controls. The OGI method can be efficacious for patients with schizophrenia.